Improving building fabric for energy efficiency in hot climates by applying passive cooling strategies: a case study for school buildings: towards environmental school buildings in hot, arid region - Mohamed, Sara A.M. (2017)
The demands for cooling in non-domestic buildings are rising throughout the world This thesis is concerned about the environmental performance of the primary schools in Khartoum State in Sudan. The Sudanese government continues to build more schools throughout the country, and particularly in the large city of Khartoum, without any consideration for the effect of the climate on the thermal comfort inside the buildings. This study focused on the thermal comfort within classrooms and the improvement of the building fabric by provision of passive cooling strategies, as well as other passive ways that improve the classroom’s thermal performance. A comprehensive literature review has been conducted, including the concept of the environmental performance of school buildings and the technique of passive cooling technologies, as well as the benefit of a ventilated facade for reducing the cooling load. The literature review also helped to initially formulate possible passive measures that could be applied to the prototypes school wall fabrics, to enhance their thermal performance and adapt them for a hot and harsh climate. These passives cooling techniques ideas were investigated for further research. School buildings often have poor thermal comfort and poor indoor air quality (IAQ), which affect the pupils’ health, education and productivity. So, this research investigated the thermal performance of naturally ventilated walls when adding passive cooling to the wall fabric by using ceramic and looked into passive cooling techniques to enhance thermal comfort and the temperature and ventilation inside the classrooms. A number of different studies were undertaken and sketches of proposed techniques produced in order to achieve the intended research case design. Computational fluid dynamics (CFD) simulations have been performed in order to examine the behaviour of the cooling wall system in reducing the effect of outside air temperature under different wind velocities in the summer period, utilizing weather data for Khartoum. The work concludes that the system was capable of reducing the air temperature by up to 12C°-15 C°. The different examinations included analyzing the temperature distribution and air velocities profiles inside the classroom, highlighting the different effects of buoyancy and wind velocity when adding passive cooling to the wall façade.